MLH1 epimutation is a rare mechanism for Lynch syndrome: A case report and review of the literature. Issue 9 (15th May 2021) - Zyla, Roman; Graham, Tracy; Aronson, Melyssa; Velsher, Lea; Mrkonjic, Miralem; Turashvili, Gulisa
Abstract: Endometrial carcinoma is one of the prototypical malignancies associated with Lynch syndrome, an inherited cancer syndrome most commonly caused by germline mutations in DNA mismatch repair (MMR) genes, although rare alternative mechanisms also exist. In this report, we describe a patient first diagnosed with colorectal cancer at age 33, then vulvar squamous cell carcinoma, facial sebaceous adenoma/sebaceoma, and finally endometrial carcinoma at age 52. All tumors were MLH1/PMS2‐deficient by immunohistochemistry, and MLH1 promoter methylation was identified in the endometrial cancer. Germline MLH1 testing was negative for pathogenic variants, but she was subsequently diagnosed with Lynch syndrome secondary to a germline monoallelic constitutional epimutation of the MLH1 promoter. Identification of patients displaying a Lynch syndrome phenotype but lacking germline MMR mutations is important to avoid delays in the diagnosis of Lynch syndrome as well as the initiation of appropriate cancer screening and genetic counseling.